Aplikasi Manajemen Persediaan Barang Berbasis Economic Order Quantity (EOQ) - Taufiq Iqbal; Daniel Aprizal; Muhammad Wali (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2017)
Inventory management is an activity undertaken by a company that is needed in making decisions so that the need for materials or goods for the purposes of the company's activities both production and sales can be met optimally with the least risk possible. Over-inventory is wasteful because it causes too high loads for storage and maintenance during storage at the warehouse. This research tries to build an inventory application by applying EOQ (Economic Order Quantity) method as the base of development. This research method is divided into three stages, namely data collection pre-development, development and implementation, and data collection post-development. The result of this research is inventory application with EOQ Probabilistic method with emphasizing result with graph form to facilitate company owner in making decision. Inventory management system built using HTML, CSS, Jquery, Java Script, JSON, AJAX, Boostrap as a media in interface design. While PHP as the server side and MySQL as the database.